2011
DOI: 10.1515/cclm.2011.709
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic accuracy of two human epididymis protein 4 (HE4) testing systems in combination with CA125 in the differential diagnosis of ovarian masses

Abstract: Background: Cancer antigen 125 (CA125) is the best known single tumor marker for ovarian cancer (OC). We investigated whether the additional information of the human epididymis protein 4 (HE4) improves diagnostic accuracy. Methods: We retrospectively analyzed preoperative sera of 109 healthy women, 285 patients with benign ovarian masses (cystadenoma: ns78, leimyoma: ns66, endometriosis: ns 52, functional ovarian cysts: ns79, other: ns10), 16 low malignant potential (LMP) ovarian tumors and 125 OC (stage I: 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 37 publications
3
37
1
Order By: Relevance
“…Overall, ultrasound diagnosis of ovarian masses with increased HE4 and CA-125 suggests the presence of ovarian cancer; if only increased CA-125 is observed, the patient may have ovarian endometriosis or other benign diseases; if only increased HE4 is observed, the patient may have ovarian or endometrial cancer or other malignant tumors. Consistent with results of Chinese and worldwide studies (Moore et al, 2011;Bandiera et al, 2011;Jacob et al, 2011;Lenhard et al, 2011;Montagnana et al, 2011;Van Gorp et al, 2011;Kadija et al, 2012), our retrospective analysis showed that HE4 can be used as a marker for the diagnosis of ovarian cancer and endometrial cancer, and is more effective than using CA-125.…”
Section: Comparison Of Ca-125 Among Groupssupporting
confidence: 91%
“…Overall, ultrasound diagnosis of ovarian masses with increased HE4 and CA-125 suggests the presence of ovarian cancer; if only increased CA-125 is observed, the patient may have ovarian endometriosis or other benign diseases; if only increased HE4 is observed, the patient may have ovarian or endometrial cancer or other malignant tumors. Consistent with results of Chinese and worldwide studies (Moore et al, 2011;Bandiera et al, 2011;Jacob et al, 2011;Lenhard et al, 2011;Montagnana et al, 2011;Van Gorp et al, 2011;Kadija et al, 2012), our retrospective analysis showed that HE4 can be used as a marker for the diagnosis of ovarian cancer and endometrial cancer, and is more effective than using CA-125.…”
Section: Comparison Of Ca-125 Among Groupssupporting
confidence: 91%
“…These findings make it reasonable that the combination improved CA125 but not HE4 performance. DOI:http://dx.doi.org/10.7314/APJCP.2016.17.1.323 Tissue CA125 and HE4 Gene Expression Offers Superior Accuracy in Discriminating Benign from Malignant Pelvic Masses Several studies (Moore et al, 2008;Huhtinen et al, 2009;Moore et al, 2009;Escudero et al, 2011;Lenhard et al, 2011;Freydanck et al, 2012;Zhen et al, 2014) reported that the combination of serum HE4 with serum CA125 further enhanced the diagnostic accuracy when compared with either maker alone, suggesting that when used in combination, the two markers HE4 and CA125 complement each other, as each improves the discriminatory performance of the other. On the contrary, Jacob et al, suggested that no benefit from combining HE4 and CA125 in the clinical setting (Jacob et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have proposed that combining the measurements of serum CA125 and HE4 levels yielded a higher accuracy compared to either biomarker alone for the differential diagnosis of pelvic masses (Moore et al, 2008;Huhtinen et al, 2009;Moore et al, 2009;Escudero et al, 2011;Lenhard et al, 2011;Freydanck et al, 2012). However, it has been shown that no benefit from combining CA125 and HE4 in the clinical practice (Jacob et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of human epididymis protein 4 (HE4) has provided another biomarker to improve the preoperative diagnosis of epithelial ovarian carcinoma [21 -24] . The simultaneous determination of carbohydrate antigen (CA) 125 and HE4 with imaging represents a reliable estimate of the probability of the presence of epithelial ovarian carcinoma [22,23] .…”
Section: Tumor Markers -The Old and The Newmentioning
confidence: 99%